The Expression of Sphingosine Kinase-1 in Head and Neck Carcinoma - Facchinetti, Maria Marta (2010)
Sphingosine kinase-1 (SPHK1) modulates the proliferation, apoptosis and differentiation of keratinocytes through the regulation of ceramide and sphingosine-1-phosphate levels. However, studies on the expression of SPHK1 in human head and neck squamous cell carcinoma (HNSCC) specimens are lacking. Therefore, the aim of the present work was to evaluate SPHK1 expression in human primary HNSCCs and to correlate the results with clinical and anatomopathological parameters. We investigated the expression of this protein by immunohistochemistry performed in tissue microarrays of HNSCC and in an independent cohort of 37 paraffin-embedded specimens. SPHK1 expression was further validated by real-time PCR performed on laser capture-microdissected tissue samples. The positive rate of SPHK1 protein in the cancerous tissues was significantly higher (74%) than that in the nontumor oral tissues (23%), and malignant tissues showed stronger immunoreactivity for SPHK1 than normal matching samples. These results were confirmed by real-time PCR quantification of SPHK1 mRNA. Interestingly, the positive expression of SPHK1 was associated with shorter patient survival time (Kaplan-Meier survival curves) and with the loss of p21 expression. Taken together, these results demonstrate that SPHK1 is upregulated in HNSCC and provide clues of the role SPHK1 might play in tumor progression.